Retrofitting on Flexural Strength of RC Columns Using Polyester Resin Concrete - Dahlia Patah; Ashar Saputra; Andreas Triwiyono (Journal of the Civil Engineering Forum, 2016)
Concrete column structures damages due to flexural moment need to be repaired and strengthened to avoid of sudden failure by applying appropriate methods. The method applied in this study was retrofitting by applying polyester resin concrete. In order to know the effect of polyester resin concrete against axial load capacity, stiffness, ductility and the damage pattern of columns by eccentrically loaded, an experimental laboratory was carried out. In this study, three column specimens are tested. The dimension of the specimen is 150 mm x 150 mm and the high of the column are 1200 mm with the effective high is 600 mm and 600 mm for corbel. The column specimens have a fixed eccentricity of 50 mm. First, initial column tested before yield point of reinforcing bar reached and concrete crack limited to 0,4mm. Further, retrofitting applied to each initial column specimen using normal concrete and polyester resin concrete with the level of resin 15% and 20%, respectively. Retrofitting column tested again with the same loading of initial column until it reaches the collapse load. The result of experiment compares to analysis method by Nawy and Whitney which represent the analysis of normal concrete column capacity. The result showed that levels of resin to be used is 20% because of better workability compared to 15% resin. Further, compressive test on resin concrete cylinder showed that the resin level at 15% and 20% are 82.82 MPa and 76.65 MPa, respectively. The strength of KR-ii decreased about 33.523%. The strength of KR-15ii and KR-20ii increased 5.08% and 24.827% respectively compared to initial column. Specimen column stiffness KR-ii. KR-15ii and KR-20ii decreased about 76.22%, 24.50% and 37.65%, respectively from the initial column. Furthermore, ductility of KR-ii, KR-15ii and KR-20ii decreased about 1.512, 1.250 and 2.50, respectively. The changes of the ultimate capacity load of KR-ii, KR-15ii and KR-20ii by Nawy Method respectively -26.54%, 12.66%, and 13.83%, whereas the method of Whitney respectively -17.68%, 26.25%, and 27.56%. The use of polyester resin concrete can change the pattern of collapse from brittle to ductile columns.Keywords: retrofit, ductility, stiffness, flexural column, eccentricity